2014
DOI: 10.1007/s10803-014-2309-1
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Adaptive Behavior Skill Deficits From Childhood to Adolescence in Autism Spectrum Disorder: Role of Executive Function

Abstract: Almost half of all children with autism spectrum disorder have average cognitive abilities, yet outcome remains poor. Because outcome in HFASD is more related to adaptive behavior skills than cognitive level it is important to identify predictors of adaptive behavior. This study examines cognitive and demographic factors related to adaptive behavior, with specific attention to the role of executive function (EF) in youth with HFASD aged 4–23. There was a negative relationship between age and adaptive behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
201
4
9

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 236 publications
(237 citation statements)
references
References 32 publications
23
201
4
9
Order By: Relevance
“…In our own study, we found that time 2 ABAS scores but not time 2 SRS scores were significantly improved from mean time 1 scores. In contrast to our findings, several recent studies have found that samples of individuals with ASD without intellectual disability actually show an age-related decline in adaptive behaviors as measured by the Vineland Adaptive Behavior Scales (VABS) (2,3,6,37). This difference could be due to our choice of the General Adaptive Composite scores from the ABAS rather than the VABS, or that we used longitudinal data rather than performing a cross-sectional study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In our own study, we found that time 2 ABAS scores but not time 2 SRS scores were significantly improved from mean time 1 scores. In contrast to our findings, several recent studies have found that samples of individuals with ASD without intellectual disability actually show an age-related decline in adaptive behaviors as measured by the Vineland Adaptive Behavior Scales (VABS) (2,3,6,37). This difference could be due to our choice of the General Adaptive Composite scores from the ABAS rather than the VABS, or that we used longitudinal data rather than performing a cross-sectional study.…”
Section: Discussioncontrasting
confidence: 99%
“…Others reported more modest numbers for these predictors, with IQ predicting 3% of variance in outcome and language ability predicting 32% of variance in outcome (14). A study that included only individuals with ASD without cooccurring intellectual disability found age and IQ as weaker predictors, predicting 6-28% of various adaptive behavior subscales (6). Although these previous studies have been successful in predicting these outcomes using behavioral measures, in most cases, the majority of the variance in outcomes remains unexplained.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Previous research proposed typical and atypical developmental trajectories of distinct EFs in ASD with intact performance for prepotent response inhibition tasks, planning tasks and set-shifting tasks in older youths with ASD, but no age-moderating effect for spatial working memory or interference control tasks [12,18,19]. Additionally, several studies found an association between executive functions and adaptive behavior [20][21][22][23][24][25]. Compared with clinical psychometric tests of EFs, the MPT do not draw on academic skills that may vary considerably across different age-groups and may, therefore, better apt to disentangle more specific processes of EFs in juvenile AS (please see [5] for more details) and thus may be especially useful to study the association between executive functions and adaptive behavior in ASD with no intellectual deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Adaptive functioning is the usual performance of daily life activities and it is considered the ability to convert cognitive potential into real world skills Pugliese [10]. The American Association on Mental Retardation (AAMR) defined adaptive behavior as "the collection of conceptual, social, and practical skills that have been learned by people in order to function in everyday lives" Matson & Glidden [11].…”
Section: Introductionmentioning
confidence: 99%